2016
DOI: 10.1055/s-0041-110770
|View full text |Cite
|
Sign up to set email alerts
|

Video capsule endoscopy completion and total transit times are similar with oral or endoscopic delivery

Abstract: Background and study aims: Video capsule endoscopy (VCE) is limited by incomplete procedures. There are also contraindications to the standard ingestion of the capsule that require endoscopic placement. Our aim was to compare the study completion rate of VCE after oral ingestion and endoscopic deployment. Patients and methods: We performed a review of all VCE from April 2010 through March 2013. Inpatient and outpatient cohorts grouped by the method of capsule delivery were formed and compared. Multivariable lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
2
7
1
Order By: Relevance
“…In the present study, the SBTT in the prucalopride group was substantially shorter than the SBTT reported in the literature for both inpatient and outpatient VCE. Furthermore, the completion rate in the prucalopride group was also substantially higher than the completion rate reported in the literature for the inpatient VCE and is comparable to the completion rates for outpatient VCE [ 9 11 ]. For the control group, the SBTT and completion rate were similar to what is reported in the literature [ 7 9 , 11 ].…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…In the present study, the SBTT in the prucalopride group was substantially shorter than the SBTT reported in the literature for both inpatient and outpatient VCE. Furthermore, the completion rate in the prucalopride group was also substantially higher than the completion rate reported in the literature for the inpatient VCE and is comparable to the completion rates for outpatient VCE [ 9 11 ]. For the control group, the SBTT and completion rate were similar to what is reported in the literature [ 7 9 , 11 ].…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, the completion rate in the prucalopride group was also substantially higher than the completion rate reported in the literature for the inpatient VCE and is comparable to the completion rates for outpatient VCE [ 9 11 ]. For the control group, the SBTT and completion rate were similar to what is reported in the literature [ 7 9 , 11 ]. Therefore, the differences in the SBTT and the completion rates between the two groups in our study did not result from disproportionately longer SBTT and lower completion rate in the control group biasing the results in favor of the prucalopride group.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…A single center study reported a higher completion rate and diagnostic yield when a real time viewer was used and the capsule was placed endoscopically into the duodenum in the case of prolonged gastric transit time (> 60 min)[35]. The unselected primary endoscopic placement of the capsule into the duodenum to circumvent possible gastroparesis had no effect on complete small bowel visualization in a single center analysis of 687 hospitalized or out-patients compared to swallowing the capsule[36]. In a prospective single-center study including 100 VCE studies, a pathologic Gastroparesis Cardinal Symptoms Index questionnaire could not predict a prolonged gastric transit time nor did a delayed gastric passage have any clinical significance[37].…”
Section: Vce In Patients With Motility Disordersmentioning
confidence: 99%